THE CONCEPT OF CULTIVATING A SINCERE ATTITUDE FOR AN EDUCATOR IN THE CONTEXT OF SELF-DEVOTION TO BIRTH AN ISLAMIC GENERATION - Muttaqin, M. Imamul; Sholihah, Tsaniyatus; Atsaniyah, Filosofia; 'Asyiroh, Nahdliana 'Aisyatul; Khudin, Ahmad Mifta; Muttaqien, Muhammad Faizul (al-Iltizam: Jurnal Pendidikan Agama Islam, 2023)
Lately, many people have been known to get jobs as educators because they think that teaching is a profession that is easy to get and only needs to teach. So they carry out their work without full sincerity, do not know the true meaning of self-devotion, and are only concerned with the salary they get. For this reason, this research is intended to examine the concept of cultivating a sincere attitude for educators to give birth to an Islamic generation. The research method used is Library Research by taking from various journals and books related to the above problems. The result of this research is that in order to instill a sincere attitude in every educator, an understanding of the importance of awareness of the teaching profession as a form of self-devotion should be instilled first. If an educator is sincere, there will be several things he can get, such as being a lucky person, having an eternal investment, and being a noble person in the sight of Allah SWT.